Carbon Dioxide Improves Phosphorus Nutrition by Facilitating the Remobilization of Phosphorus From the Shoot Cell Wall in Rice (Oryza sativa) - Zhu, Xiao Fang; Zhang, Xiao Long; Dong, Xiao Ying; Shen, Ren Fang (Frontiers in Plant Science, 2019)
Phosphorus (P) starvation leads to increased reutilization of cell wall P in rice (Oryza sativa). Carbon dioxide (CO2) is involved not only in plant growth and development, but also in the response to abiotic stresses. However, it remains unclear whether CO2 affects the reutilization of cell wall P in rice when subjected to P deficiency. In the present study, elevated CO2 (600 µL•L-1) significantly increased the soluble P content in shoots when compared with ambient CO2 (400 µL•L-1). This positive effect was accompanied by an increase of pectin content, as well as an increase of pectin methylesterase (PME) activity, which results in P release from the shoot cell wall, making it available for plant growth. P deficiency significantly induced the expression of phosphate transporter genes (OsPT2, OsPT6, and OsPT8) and decreased the P content in the xylem sap, but elevated CO2 had no further effect, indicating that the increased soluble P content observed in shoots under elevated CO2 is attributable to the reutilization of shoot cell wall P. Elevated CO2 further increased the P deficiency-induced ethylene production in the shoots, and the addition of the ethylene precursor 1-amino-cyclopropane-1-carboxylic acid (ACC) mimicked this effect, while the addition of the ethylene inhibitor aminoethoxyvinylglycine (AVG) abolished this effect. These results further support the role of ethylene in the alleviation of P deficiency under elevated CO2. Taken together, our results indicate that the improvement of P nutrition in rice by elevated CO2 is mediated by increasing the shoot cell wall pectin content and PME activity, possibly via the ethylene signaling pathway.